2008
DOI: 10.1371/journal.pone.0002262
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications of Plasma Membrane Condensation for T Cell Activation

Abstract: The T lymphocyte plasma membrane condenses at the site of activation but the functional significance of this receptor-mediated membrane reorganization is not yet known. Here we demonstrate that membrane condensation at the T cell activation sites can be inhibited by incorporation of the oxysterol 7-ketocholesterol (7KC), which is known to prevent the formation of raft-like liquid-ordered domains in model membranes. We enriched T cells with 7KC, or cholesterol as control, to assess the importance of membrane co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 46 publications
6
95
0
Order By: Relevance
“…We have previously reported that engagement and signaling through the TCR reorganizes the membrane at these sites to yield highly ordered domains (40). In addition, we observed a similar relationship as found in this study, in which ex vivo lipid manipulations of Jurkat T cells decrease the membrane order specifically at the T cell activation site, impairing IL-2 production and secretion (25).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We have previously reported that engagement and signaling through the TCR reorganizes the membrane at these sites to yield highly ordered domains (40). In addition, we observed a similar relationship as found in this study, in which ex vivo lipid manipulations of Jurkat T cells decrease the membrane order specifically at the T cell activation site, impairing IL-2 production and secretion (25).…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown that disrupting membrane condensation at the T cell activation site inhibits T cell signal transduction and downstream effector functions in vitro (25). In this study we examined the impact of dietary lipids on T cell lipid composition and membrane order and how this correlates to in vivo and ex vivo T cell responses, specifically in the absence of obesity and obesity-induced inflammation.…”
mentioning
confidence: 99%
“…That the T cell plasma membrane of fixed cells that are in contact with beads coated with anti--CD3 antibody is more ordered than the rest of the T cells plasma membrane, has been demonstrated by studying laurdan generalised polarisation [16,17]. In a very recent study by the same group, it was demonstrated that lipids expected to form lipid rafts like cholesterol, sphingomyelin and PC with saturated acyl chains accumulate where T cells interact with beads covered in antibodies against the T cell receptor [21].…”
Section: Discussionmentioning
confidence: 99%
“…If this holds for cell plasma membranes, cholesterol depletion could lead to the aggregation of lipid rafts. That cholesterol and the capability to form raft--like liquid ordered domains are important for membrane condensation (the existence of ordered domains), at the contact site between T cells and beads coated with T cell antigen receptor (TCR) stimulating antibodies, has been demonstrated in fixed cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10-20 circular areas per condition, corresponding to the ciliary base, were selected on the basis of galectin-3 staining. Generalized polarization values were non-linearly fitted to a Gauss distribution using a custom-built macro in ImageJ (Rentero et al, 2008).…”
Section: Laurdan Cell Microscopymentioning
confidence: 99%